GILLNET SELECTIVITY STUDY ON LOMEK FISHING IN VILLAGE OF ALAI DISTRICT, MERANTI ISLANDS - Samuel Firmando Pakpahan; Arthur Brown; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTDevelopment of tools cather fish mush be selective to decrease the insignifcant fish get caught, so the fish that caught already fulfill the criteria of eligible catch fish. This research was conducted in Alai Village, Meranti Islands Regency, as a purpose to analyst the gillnet selectivity level of 3 inches and 4 inches. The results show that the 3 inch mesh size the higher the catch size (above 20 cm) the lower the capture ratio and the 4 inch mesh size the higher the catch size (above 20 cm) the higher the catch ratio. Keywords : Gill Nets , Lomek Fish, How to Catch Fish, Nets Selectivity